2019
DOI: 10.1111/iwj.13281
|View full text |Cite
|
Sign up to set email alerts
|

Patient education materials on pressure injury prevention in hospitals and health services in Victoria, Australia: Availability and content analysis

Abstract: Pressure injuries (PIs) are a common quality indicator for hospital care, and preventing PIs often requires patient engagement; as such, Australian consensus research has recommended that high‐quality education materials be made to patients for PIs via hospital networks. The purpose of the present study was to assess the availability and accuracy of patient education materials on PIs in publicly available hospital websites in Victoria, Australia. Two independent coders assessed 212 websites for content on PI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 62 publications
3
21
0
3
Order By: Relevance
“…Moreover, the PPIPCB is delivered individually to the participant, increasing the potential to improve PIP knowledge and participation in PIP care 55 . As nurses play a vital role in patient education, having easy access to targeted evidence-based patient education resources can facilitate interpersonal dialogue between nurses and patients to enhance participation in their care 23,25,40 . Therefore, understanding why PIP education is not effectively delivered by nurses warrants further investigation to support the role of care bundles as a PIP strategy.…”
Section: Patients' Participation In Their Pip Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the PPIPCB is delivered individually to the participant, increasing the potential to improve PIP knowledge and participation in PIP care 55 . As nurses play a vital role in patient education, having easy access to targeted evidence-based patient education resources can facilitate interpersonal dialogue between nurses and patients to enhance participation in their care 23,25,40 . Therefore, understanding why PIP education is not effectively delivered by nurses warrants further investigation to support the role of care bundles as a PIP strategy.…”
Section: Patients' Participation In Their Pip Educationmentioning
confidence: 99%
“…Research shows most patients are willing participants in their PIP care 7 such as decision-making and care planning [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Participants trusted healthcare professionals more than any other source of health information. Considering the lack of wound-related information for patients in general, 52,53 all information on VLU management provided to patients as part of research participation was valued by research participants as they acknowledged this improved their understanding of VLU healing and future prevention and care, which they considered as part of research-related quality care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to consumers' involvement in research, we involve them in assessment and development of education materials. For example, we conducted a small-scale research project on the availability and content analysis of online patient education materials on PI prevention in hospitals and health services in Melbourne Metropolitan and rural Victoria (60). We found that a greater proportion of hospitals did not have any of these materials publicly available, with private hospitals and metropolitan hospitals more likely to have materials available on their sites compared with public and rural hospitals.…”
Section: Consumer Involvementmentioning
confidence: 98%
“…We found that a greater proportion of hospitals did not have any of these materials publicly available, with private hospitals and metropolitan hospitals more likely to have materials available on their sites compared with public and rural hospitals. The available materials contained accurate messages on PI defining characteristics and risk factors for PIs, although many of these materials were not approved by a consumer group (60). We plan to develop a repository of patient education materials on PI prevention, which will be regularly updated and approved by the Consumer Advisory Group.…”
Section: Consumer Involvementmentioning
confidence: 99%